Review of the genus Kisaura Ross 1956 (Trichoptera: Philopotamidae) from India - Pandher, Manpreet Singh; Kaur, Simarjit; Parey, Sajad Hussain (Zootaxa, 2020)
This paper synthesizes knowledge of caddisflies belonging to the genus Kisaura Ross 1956 from India. The study is based on collection expeditions undertaken since 2008 in streams of the Indian Himalayan region and some of its contiguous states. The species newly described here include Kisaura sangtam sp. nov. (Nagaland); K. acuta sp. nov., (Uttarakhand); and K. rotunda sp. nov. and K. teestaensis sp. nov. (both from Sikkim). Species reported for the first time from India include Kisaura longispina (Kimmins 1955) (from Uttarakhand); K. laban Malicky & Chantaramongkol 2009 (in Malicky 2009, Arunachal Pradesh); K. rossi (Kimmins 1955) (from Sikkim, Mizoram, Himachal Pradesh, Arunachal Pradesh); K. surasa Malicky & Chantaramongkol 1993 (Uttarakhand); K. filiformis Mey 1996 (from Himachal Pradesh); K. pectinata (Ross 1956) (from West Bengal); and K. intermedia (Kimmins 1955) and K. cina Malicky & Chantaramongkol 1993 (both from Arunachal Pradesh). With these additions the genus Kisaura is represented by 39 species, 35 of which have been described previously (27 described originally from India and 8 new records for India) and 4 are new species.